CO2 laser irradiation for debonding ceramic orthodontic brackets - Matos,Denise Souza (2021)
Abstract This study evaluated shear bond strength (SBS), adhesive remnant index (ARI) and fracture mode of chemically and mechanically retained ceramic brackets bonded with different composite resins and irradiated with CO2 laser. The null hypothesis was that ceramic brackets bonded with different composite resins and irradiated with CO2 laser would have similar SBS values. Ninety human premolars were divided into four experimental groups according to the combination of type of composite resin (Transbond XT and Z 250) and type of ceramic bracket (Fascination and Mystique), and two control groups (n=15). In the four experimental groups, the brackets were irradiated with CO2 laser at 10 W for 3 seconds before SBS testing. Enamel surface ARI was calculated after debonding under electron microscopy scanning. ANOVA and the Mann-Whitney test were used for statistical analysis. The laser groups had lower SBS values than the non-irradiated groups (control) (p<0.05). The mechanically retained brackets (Mystique) had the higher (p<0.05) and Z250 had the lower SBS values after CO2 laser irradiation. The groups bonded with Z250 had the highest ARI. Adhesive fractures were the most prevalent. The null hypothesis was rejected. CO2 laser decreased SBS efficiently and facilitated debonding of mechanically and chemically retained ceramic brackets.